WeMen - Antoniou, Klitsa (My University, 2026)
Egomio for the arts and the culture Choreography Platform 2019, Limassol Cyprus Rialto Theatre Video Art: Klitsa Antoniou Choreography Elena Christodoulidou https://vimeo.com/375277553